2009
DOI: 10.1128/jvi.00702-09
|View full text |Cite
|
Sign up to set email alerts
|

The Genome of Human Parvovirus B19 Can Replicate in Nonpermissive Cells with the Help of Adenovirus Genes and Produces Infectious Virus

Abstract: Human parvovirus B19 (B19V) is a member of the genus Erythrovirus in the family Parvoviridae. In vitro, autonomous B19V replication is limited to human erythroid progenitor cells and in a small number of erythropoietin-dependent human megakaryoblastoid and erythroid leukemic cell lines. Here we report that the failure of B19V DNA replication in nonpermissive 293 cells can be overcome by adenovirus infection. More specifically, the replication of B19V DNA in the 293 cells and the production of infectious progen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
124
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(125 citation statements)
references
References 53 publications
1
124
0
Order By: Relevance
“…In agreement with these results, adenovirus 2 facilitated DNA replication of the closely related parvovirus MVM, 27 whereas pXX6 adenoviral vector, enabled the erythrovirus B19 to replicate its DNA and produce infectious progeny particles in non-permissive HEK 293 cells. 25 This led us to speculate that one or several gene products of pXX6 may directly modulate parvoviral DNA replication or set up favorable cellular conditions for that. In support of an active role of adenovirus genes in parvoviral DNA replication, it has been shown that E4(orf6) participates in the conversion of the singlestranded AAV-2 viral genome into the double-stranded replicative forms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with these results, adenovirus 2 facilitated DNA replication of the closely related parvovirus MVM, 27 whereas pXX6 adenoviral vector, enabled the erythrovirus B19 to replicate its DNA and produce infectious progeny particles in non-permissive HEK 293 cells. 25 This led us to speculate that one or several gene products of pXX6 may directly modulate parvoviral DNA replication or set up favorable cellular conditions for that. In support of an active role of adenovirus genes in parvoviral DNA replication, it has been shown that E4(orf6) participates in the conversion of the singlestranded AAV-2 viral genome into the double-stranded replicative forms.…”
Section: Discussionmentioning
confidence: 99%
“…The adenovirus genes E2a, E4(orf6) and VA RNA were found to boost human erythrovirus B19 replication and production in HEK 293 cells, an otherwise non-permissive cell line for B19 production. 25 Furthermore, parvovirus H-1PV failed to initiate replication in secondary cultures of normal human embryonic lung cells, unless these cells are co-infected with adenovirus serotype 12. 26 In addition, adenovirus serotype 2 induced an increase in parvovirus MVMp DNA replication in HeLa cells, associated with re-localization of MVMp DNA from host nucleoli to adenovirus replication factories.…”
Section: Introductionmentioning
confidence: 99%
“…AY386330) (19). The parent plasmid C1NS1(ÏȘ), which contains the SV40 replication origin and produces a prematurely terminated NS1 gene has been described previously (14,17,20). The parent plasmid pB19-N8 was described previously (19 -21).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were transfected with 2 g of DNA per 60-mm plate using Lipofectamine TM and PLUS TM reagent (Invitrogen) according to the manufacturer's instructions. UT7/Epo-S1 cells, which are permissive to B19V infection (20,25,26), were cultured in DMEM with 10% FCS and 2 units/ml of Epo (Epogen; Amgen, Thousand Oaks, CA) at 37°C in 5% CO 2 . Plasmids B19-N8, B19-N8A2-1U2AF, and B19-N8A2-1/ 2KO were digested with XhoI/EcoRI to recover the excised B19V DNA fragments that were used for electroporation.…”
Section: Cells Transfection and Virus Infection-cos-7 Cellsmentioning
confidence: 99%
See 1 more Smart Citation